The criminal minimalism of Raúl Zaffaroni and a dialogue with philosophical hermeneutics as ways for a reconstruction of the brazilian criminal justice system - Paiva, Matheus Maciel; Silva Filho, Edson Vieira da (REVISTA QUAESTIO IURIS, 2021)
The proposal of this paper is to clarify the main aspects of Raúl Zaffaroni’s thought about his theoretical model of the criminal justice system, which fits a criminal minimalism. In the same way, it’s to demonstrate a close study between the proposal of Zaffaroni and the current Brazilian constitutionalism, particularly under the perspective on hermeneutics. In general, it uses descriptive and analytical methods with statistical data to describe the reality of the criminal policy in Brazil. Moreover, it is necessary to keep in mind the phenomenology present in the final stages of this paper. The most important aspects of the author’s idea are the realism of marginalism and the colonialism/neocolonialism. As a result of these two elements there is a possibility of achieving the rescue of the facticity and the history of Latin America’s reality. This aspect converges with the proposal of hermeneutics with existential phenomenology, that is to say, it has as a base the philosophy of existential analysis or fundamental ontology. Therefore, it is concluded that the use of hermeneutics to understand and interpret the constitutional text is an appropriate way to correct the current paradigm shift, as well as reconstructing the criminal justice system properly.